2018
DOI: 10.1007/s10461-018-2295-y
|View full text |Cite
|
Sign up to set email alerts
|

HIV Treatment Cascade by Housing Status at Enrollment: Results from a Retention in Care Cohort

Abstract: Though housing instability is linked to poor HIV health outcomes, studies that assess the HIV treatment cascade by housing status are limited. Using data from a multi-site Retention in Care initiative we constructed HIV treatment cascades for participants (n=463) of five grantee sites. We found no significant differences in viral suppression at follow-up among participants who were unstably housed at enrollment (49%) as compared to those who were stably housed at enrollment Conflict of Interest: The authors de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Housing instability is a result of a complex interplay between individual vulnerabilities and broader structural factors. However, multiple randomized controlled trials have found providing housing assistance to independently improve outcomes among PLWH who experience housing instability [61,62], and thus it is a modifiable contextual factor [54,63]. To increase access to housing services for PLWH, the Health Resources and Services Administration recommends building new partnerships between public and private stakeholders, funding innovative strategies to address housing needs in PLWH, and involving PLWH with housing needs in this process [64].…”
Section: Discussionmentioning
confidence: 99%
“…Housing instability is a result of a complex interplay between individual vulnerabilities and broader structural factors. However, multiple randomized controlled trials have found providing housing assistance to independently improve outcomes among PLWH who experience housing instability [61,62], and thus it is a modifiable contextual factor [54,63]. To increase access to housing services for PLWH, the Health Resources and Services Administration recommends building new partnerships between public and private stakeholders, funding innovative strategies to address housing needs in PLWH, and involving PLWH with housing needs in this process [64].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers modified the cascade for various reasons. First, data availability, which affects mostly stages included; for example, some studies started with PLHIV linked in care, [50][51][52] while others did not have viral load data. 53 In articles that used longitudinal design and multistate methods, the lack of transfer-out information 8 and failure to capture re-engagement in care after LTFU 46 affected the inclusion of these stages.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of interest was progression through the HIV cascade of care. Using data from the confidential linkage to the Drug Treatment Program, we categorized participants into their stage of the HIV cascade of care using a priori definitions from previous studies [28,33,34]. At each semi-annual study visit, participants were assigned to one of five potential stages of the HIV cascade of care: unlinked to HIV care, included participants without HIV VL and CD4 þ cell count measurements conducted in the community and without any ART dispensations in the 6 months prior to the study visit; linked to HIV, care included participants with at least one community-based HIV VL or CD4 þ cell count measurement and 0 days of ART dispensation in the last 6 months; on ART, which included participants with at least one day of ART dispensation in the last 6 months; adherent to ART, included participants with at least 171 days of ART dispensation, corresponding to 95% adherence in the previous 6 months; and VL suppressed, which included participants with <50 copies/ml plasma at the most recent HIV VL analysis [33].…”
Section: Methodsmentioning
confidence: 99%
“…Homelessness has also been linked to increases in the intensity of alcohol and illicit drug use that can exacerbate HIV risk, interfere with ART adherence and hasten HIV disease progression [18,[24][25][26]. Previous systematic reviews have found strong evidence that exposure to marginal housing environments was associated with HIV risk behaviour, HIV acquisition, suboptimal HIV care and increased risk of mortality [22,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%